2010
DOI: 10.1523/jneurosci.1037-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative Auditory Fear Learning Requires Both Tuned and Nontuned Auditory Pathways to the Amygdala

Abstract: The auditory system has two parallel streams in the brain that have been implicated in auditory fear learning. The lemniscal stream has selective neurons that are tonotopically organized and is thought to be important for sound discrimination. The nonlemniscal stream has less selective neurons, which are not tonotopically organized, and is thought to be important for multimodal processing and for several forms of learning. Therefore, it has been hypothesized that the lemniscal, but not the nonlemniscal, pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 33 publications
6
53
1
Order By: Relevance
“…One possibility is that the association between cortical and thalamic projection is necessary for a discriminative form of fear learning. Although the activation of either the cortical or thalamic input is sufficient for fear-conditioning learning (Campeau and Davis, 1995;Kwon and Choi, 2009), in auditory discriminative fear learning, coactivation of both inputs might be necessary for discrimination (Antunes and Moita, 2010). This observation is consistent with a cooperative interaction between the cortical and thalamic inputs.…”
Section: Discussionsupporting
confidence: 67%
“…One possibility is that the association between cortical and thalamic projection is necessary for a discriminative form of fear learning. Although the activation of either the cortical or thalamic input is sufficient for fear-conditioning learning (Campeau and Davis, 1995;Kwon and Choi, 2009), in auditory discriminative fear learning, coactivation of both inputs might be necessary for discrimination (Antunes and Moita, 2010). This observation is consistent with a cooperative interaction between the cortical and thalamic inputs.…”
Section: Discussionsupporting
confidence: 67%
“…Together, our data revealed that auditory fearful memories are specifically consolidated at the auditory cortex level, whereas thalamic nuclei are not necessary for this process. Therefore, MG may be involved in the acquisition and retrieval processes, as reported previously (Campeau and Davis, 1995;Antunes and Moita, 2010;Weinberger, 2011), whereas it is dispensable for the consolidation of long-term memories.…”
Section: Auditory Cortex Is Necessary For Early Consolidation Of Recesupporting
confidence: 62%
“…According to previous studies (Poremba et al, 1997(Poremba et al, , 1998Bao et al, 2001;Sacco and Sacchetti, 2010;Cambiaghi et al, 2015;Grosso et al, 2015b), Te2 is essential for the encoding of the association between a tone and its emotional/motivational learned charge, not merely for the processing or encoding of the physical attribute of the CS. The fact that only the combined, not the individual, blockade of Te2 and Te1 impaired recent memory consolidation suggests that Te1 participates in memory information.…”
Section: Discriminative Fear Memory Processes In the Absence Of The Amentioning
confidence: 99%
“…As ACx and MGN inputs can convey distinct information to the LA and play different roles in discriminative fear conditioning (Antunes and Moita, 2010), we examined these pathways separately and found that the AMPA/NMDA ratio was significantly higher in the FC group than in the NS group in the ACx-LA pathway (p < 0.05, unpaired t test; Figures S5D-S5F), but not in the MGN-LA pathway (p = 0.63, unpaired t test; Figures S5G and S5H), indicating postsynaptically expressed LTP was selectively induced in the ACx-LA pathway in discriminative fear learning. In the ACx/MGN inputs to the amygdalo-striatal transition area (ASt), we did not detect significant difference in the AMPA/NMDA ratio between groups (p = 0.35, unpaired t test; Figures S5I-S5K), suggesting that LTP associated with discriminative fear learning is pathway specific.…”
Section: La Neuronal Ensemble Defined By Presynapticmentioning
confidence: 99%